Barriers and Facilitators to Completion of an Undergraduate Nursing Program: Exploration of Mindfulness, Mindlessness, and Retention Among Ethnic Minorities - (:unkn) unknown (My University, 2016)
As the United States population continues to grow and diversify, so too must the nursing workforce in order to meet the challenging healthcare needs of a diversifying population. Currently the nursing profession is overwhelmingly White, with only 25% of registered nurses identifying as ethnic minority (Robert Wood Johnson Foundation (RWJF), 2016). Research suggests that a diverse nursing workforce benefits many segments of the population, where better care is provided because the nurse reflects the ethnic or racial background of their patient (Glazer, Clark, & Bankston, 2015; RWJF, 2016). In order to continue to diversify the nursing profession, a pipeline of qualified ethnic minority students must be recruited and trained by colleges and universities. The challenge however, is to ensure ethnic minority students that are recruited in these programs are provided adequate resources to assist them in completing their program of study. The purpose of this study was to explore perceptions of barriers and facilitators to successful completion of an undergraduate nursing program among a sample of ethnic minority undergraduate nursing students. Suggestions of strategies to enhance retention and completion of an undergraduate nursing program were also gathered from participants. Because many of these young adults are faced with a myriad of challenges in completing their nursing program, some of which may be developmentally and psychologically related, a secondary aim of this study was to explore the concepts of mindfulness and mindlessness within the context of ethnic minority nursing students’ struggles and successes while enrolled in a nursing program. Cross-sectional qualitative in-depth interviews were conducted with undergraduate nursing students (N=20) who self-identified as ethnic minority. Participants were recruited from a large Midwestern urban university’s college of nursing and were interviewed. The transcripts of interviews were analyzed using thematic analysis. Findings emerging from data analysis were grouped into three broad themes: 1) Barriers to successful completion of an undergraduate nursing program; 2) Facilitators to successful completion of an undergraduate nursing program; and 3) Strategies to assist in program completion. While experiences in their nursing programs were positive, the study findings captures a process of traveling to a foreign country unprepared and not knowing all of the rules that govern the country. Participants shared stories of feeling lost and isolated and having some difficulties in navigating the ‘country’ of college and a larger university with only a faulty compass to guide them. Having a map to ease their navigation would help alleviate the barriers they encountered moving through their nursing program. With the current implementation of the Affordable Care Act in which many individuals including ethnic minorities are now beginning to have access to health care, there is a need for diversifying the nursing workforce (American Nurses Association, 2014). Recruiting and training more ethnic minority nurses will also be critical in caring for an aging diverse population. Amidst the budget cuts at many state universities, one finding from this study suggest the need to maintain and expand existing support services for ethnic minority students in order to increase the number of ethnic minority students graduating and entering the nursing workforce. Finding ways however, to ensure that these programs are cost-effective is an important factor to consider. Gathering information from the students themselves is an important way for university administrators to develop culturally appropriate programs that would provide rich learning experiences to support and retain ethnic minority students.
Keywords: Barriers; Ethnic Minority; Facilitators; Mindfulness; Mindlessness; Retention